1990
DOI: 10.1021/la00096a018
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity of molten salts in the presence of oil and surfactant

Abstract: The nonaqueous system of molten salts, sodium dodecyl sulfate (SDS), 1-pentanol, and decane is studied with electrical conductivity measurements in the molten salt rich emulsion phase. The molten salts are a nitrate mixture of ethylenediamine/ammonia/potassium in a ratio of 50/42.5/7.5 by weight. The addition of alcohol to a fixed ratio of salts/surfactant/oil initially causes the conductivity to decrease and then to increase; the solution also exhibits a change from turbid to clear to increasing turbidity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous to this, a microemulsion was prepared by Chang in 1990 using a molten salt mixture of ethylenediamine, ammonia and potassium as one solvent. 122 In this microemulsion, the second solvent phase was decane, with SDS used as a surfactant, and the effect of 1-pentanol on the microemulsion was explored. 122 From 2004, the groups of Zheng et al and Han et al have reported on the microemulsions formed using the ionic liquid of either BMIm BF 4 or BMIm PF 6 , mostly the surfactant Triton X-100 (TX-100) and a range of non-polar solvents or water as the second solvent phase.…”
Section: Microemulsions Containing Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous to this, a microemulsion was prepared by Chang in 1990 using a molten salt mixture of ethylenediamine, ammonia and potassium as one solvent. 122 In this microemulsion, the second solvent phase was decane, with SDS used as a surfactant, and the effect of 1-pentanol on the microemulsion was explored. 122 From 2004, the groups of Zheng et al and Han et al have reported on the microemulsions formed using the ionic liquid of either BMIm BF 4 or BMIm PF 6 , mostly the surfactant Triton X-100 (TX-100) and a range of non-polar solvents or water as the second solvent phase.…”
Section: Microemulsions Containing Ionic Liquidsmentioning
confidence: 99%
“…122 In this microemulsion, the second solvent phase was decane, with SDS used as a surfactant, and the effect of 1-pentanol on the microemulsion was explored. 122 From 2004, the groups of Zheng et al and Han et al have reported on the microemulsions formed using the ionic liquid of either BMIm BF 4 or BMIm PF 6 , mostly the surfactant Triton X-100 (TX-100) and a range of non-polar solvents or water as the second solvent phase. There was a particular focus on the characterisation of the microemulsions, including phase diagrams, and development of reliable characterisation techniques.…”
Section: Microemulsions Containing Ionic Liquidsmentioning
confidence: 99%
“…Efforts have been made to replace water by a mixture of molten salts (nitrate mixtures of ethylenediamine/ammonia/ potassium) in a system composed of sodium dodecyl sulfate (SDS), 1-pentanol and decane. 18 In recent years, attempts have alsobeenmadetoformulatenonaqueousreversemicroemulsions [19][20][21][22][23][24] containing RTILs as polar micro-environment. Recently, microemulsions, where ILs are used as oil substitutes, water substitutes, additives, or surfactants have been reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to replace water by a mixture of molten salts (nitrate mixtures of ethylenediamine/ammonia/potassium) in a system composed of sodium dodecyl sulfate (SDS), 1-pentanol and decane . In recent years, attempts have also been made to formulate nonaqueous reverse microemulsions containing RTILs as polar micro-environment.…”
Section: Introductionmentioning
confidence: 99%